ESTUDO TEÓRICO E COMPUTACIONAL DO ELETRÓLITO SÓLIDO Li3OCl PARA BATERIAS DE ÍON DE LÍTIO. - PRADO, Rodolpho Mouta Monte (2017)
Commercial liquid electrolytes used in lithium ion batteries are flammable, so researchers have been looking for solid replacements with equal performance. Here we investigated a particular solid electrolyte, Li3OCl, presenting compatibility with the ideal anode for such batteries (Li metal), which has the potential to increase batteries’ power density, but whose ionic conductivity is still unsatisfactory, which tends to decrease their power density. Our approach involved the joint use of statistical thermodynamics and computational modeling via the GULP code, aiming gathering insights that allowed us to suggest ways to increase ionic conductivity of this material. The concentration of thermally activated vacancies in Li3OCl was found to be very low, so to increase this material’s ionic conductivity it is important to artificially generate charge carriers, by either doping or nonstoichiometry. Out of these two strategies, nonstoichiometry is probably the best one, as LiCl deficiency is expected to create lithium interstitials, which have much lower mobility than vacancies. It was also found that one can increase this material’s conductivity by orders of magnitude via epitaxial strain engineering.